The Role of Ice Breaking on Increasing Students' Creativity in Learning Cultural Arts in Elementary Schools - febby yolanda; Elizar; Yasinta Mahendra (International Journal of Elementary Education, 2025)
Art and Culture learning in Elementary Schools often faces the challenge of a monotonous and less interactive classroom atmosphere, which can hinder student creativity. This study aims to examine the effectiveness of ice-breaking activities in developing students' creativity in Art and Culture learning at the Elementary School level. The method used in this research is a systematic literature review (SLR), which collects and analyzes various studies published between 2020 and 2024. The results show that the implementation of ice-breaking activities significantly increases student learning motivation, focus, and creativity. Additionally, these activities help to overcome boredom, boost student confidence, and strengthen social interaction in the classroom. However, it's important to remember that ice-breaking activities must be tailored to student characteristics and learning objectives to have optimal educational value. Therefore, educators are advised to integrate ice-breaking activities as part of innovative learning strategies to develop student creativity in Elementary Schools.